Andaman and Nicobar Administration New Five Year Plan (1978-83) Sector Agriculture Draft Annual Plan 1978-79 - Planning Commission (Planning Commission, 1977)
To bring all the paddy area suitable for dwarf H.Y.V. of paddy under the latest strain of paddy and to see that the seeds with each cultivator is replaced each fifth year. be To make, the seeds of H.Y.V. of paddy seeds, for medium and up lands and improved local strains for low-lying area, available ,to cultivators. Establishment of 20 hect. seeds multiplication farms to ensure multiplication and timely supply of H.Y.V. of paddy seeds in collaboration.
Andaman and Nicobar Administration
Keywords: Andaman and Nicobar Administration; High Yielding Variety Programme; Details of estimated expenditure; Machinery and implements; Miscellaneous; Principal Targets to be achieved; Strengthening of Soil Testing Laboratory; Sector Agriculture Production; Extending credit facilities to the cultivators; Soil Conservation